ANTES DA CHUVA: ENREDAMENTOS ENTRE TEMPO E MITO NA NARRATIVA CINEMATOGRÁFICA - LICHINSKI, TATIANE (2017)
ABSTRACT: From the concept that myth is the basis of culture texts (CONTRERA, 1996) and a complex system consisting of narrative, ritual, time, totem and magic (CAMARGO, 2013), the objective of this research is to give visibility to the entanglements between time and myth present in the narrative of the film Before the Rain, 1994, Directed by Milcho Manchevski. Its choice is justified because it is a work whose central theme is the relationship of man with time and its (non-linear) construction to entangle at least three temporalities: historical time, film time and mythical time. Therefore, we seek to know different rationales over time in various areas to conduce towards time built by literature, art that approaches cinema in terms of diegetic creation, mythic structure and archetypal elements, art that prepared the man for consumption cinema, working as an aesthetic memory aids or sharpens the need for symbolic gift in the eyes of the contemporary urban man. Therefore, we seek to know different rationales over time in various areas to we conduct in the sense of time built by literature, art that approaches cinema in terms of diegetic creation, mythic structure and archetypal elements, art that prepared the man for consumption of cinema, functioning as aesthetic memory that helps or sharpens the need for the symbolic present in the contemporary urban man's eyes. The methodology used is the film analysis of Vanoye and Goliot-Lété (1994) which presupposes the decomposition of the film into parts and then understand its role in relation to the signifying whole, with the support of the critical looks on the speeches of images, sounds, dialogues, composition of characters. An approximation between the hero's theory of the journey (CAMPBELL, 2007) and the composition of the protagonist of the film also served as a method to verify the relations between cinema with the mythical ancestor narratives, cultural memory that still persists in the current audio-visual narratives. As a final result, we enter the senses of time in the cinema so that, in our interpretation, we can point out the points of connection between time and myth in cinema.